Europe unknown. - Rottenberg, Anda; Cesarski, Wojciech; Mikina, Ewa; Palac Sztuki, Krakow (Krakow : Ministry of culture of the republic of Poland, 1991)
Agut, Pep ; Bajic, Mrdan ; Balka, Miroslaw ; Birsel, Selim ; Van Caeckenbergh, Patrick ; Cisarovsky, Tomas ; Doherty, Willie ; Duprat, Hubert ; ellberg, Carin ; Elmgreen, Michael ; Geiersinger, Werner ; Guzman, Frederico ; Günther, Ingo ; Hadzifejzovic, Jusuf ; Höller, Carsten ; et al.
Palac Sztuki TPSP, Krakow, 22/5-30/6 1991
Exhibition on the occasion of CSCE Symposium on cultural heritage, Krakow'91.
kunstcatalogus